Resin composition containing biomass-derived raw material and use thereof
A resin composition using biomass-derived ethylene to create a carbon-neutral polyolefin addresses the need for environmentally friendly materials by matching the physical properties of fossil fuel-derived resin compositions, making it suitable for diverse applications.
Patent Information
- Application Number
- JP2021020965
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2021-02-12
- Publication Date
- 2025-04-08
- Estimated Expiration
- 2041-02-12
AI Technical Summary
There is a need for a resin composition that uses biomass-derived ethylene to produce a carbon-neutral polyolefin, which is comparable to resin compositions made from conventional fossil fuel-derived materials in terms of physical properties such as adhesion.
The resin composition comprises a biomass-derived polyolefin (A) obtained by polymerizing a monomer component mainly made of ethylene derived from biomass, and a fossil fuel-derived polyolefin (B) that includes a modified polyolefin (B-1), with the structural unit derived from biomass ethylene present in an amount of 50% by mass or more.
This approach allows for the production of a polyolefin resin composition that is carbon-neutral, comparable in physical properties to those made from fossil fuels, and suitable for various applications such as films, laminated films, tubes, and bottles.
Smart Images

Figure 0007658752000001
Abstract
Description
[Technical field]
[0001] The present invention relates to a resin composition containing a biomass-derived raw material and uses thereof. [Background technology]
[0002] In recent years, due to growing awareness of the need to prevent global warming and reduce the use of petroleum, a dwindling resource, there has been a desire to replace conventional fossil fuel-derived plastic materials with carbon-neutral plant-derived plastic materials, and the use of biomass has been attracting attention.
[0003] Biomass is an organic compound that is photosynthesized from carbon dioxide and water, and can be converted back into carbon dioxide and water by using it, making it a so-called carbon-neutral renewable energy. Recently, the practical application of biomass plastics made from these biomass materials has progressed rapidly, and attempts are being made to produce various resins from biomass materials.
[0004] As for biomass-derived resins, Braskem began manufacturing and selling high-pressure low-density polyethylene (LDPE), linear low-density polyethylene (LLDPE), and high-density polyethylene (HDPE) in 2011. Using such biomass-derived LDPE, LLDPE, and HDPE to replace conventional fossil fuel-derived polyethylene is being considered (see Patent Documents 1 and 2). [Prior art documents] [Patent documents]
[0005] [Patent Document 1] JP 2012-167172 A [Patent Document 2] JP 2013-091259 A Summary of the Invention [Problem to be solved by the invention]
[0006] The object of the present invention is to provide a resin composition containing a carbon-neutral polyolefin using ethylene derived from biomass, and to provide a polyolefin resin composition that is comparable in physical properties such as adhesion to resin compositions produced using raw materials obtained from conventional fossil fuels, and to provide uses of the resin composition. [Means for solving the problem]
[0007] The present inventors have focused on ethylene, a raw material used in polyolefin resin adhesives, and have found that polyolefin resin compositions using biomass-derived ethylene as a raw material instead of ethylene obtained from conventional fossil fuels, and films, laminated films, laminates, tubes, bottles, etc. containing said resin compositions, have physical properties such as adhesiveness that are comparable to those of polyolefin resin compositions, films, laminated films, laminates, tubes, bottles, etc. produced using ethylene obtained from conventional fossil fuels. The present invention is based on such findings, and includes, for example, the following aspects [1] to
[14] .
[0008] [1] A biomass-derived polyolefin (A) obtained by polymerizing a monomer component mainly composed of biomass-derived ethylene (x); (B) a fossil fuel-derived polyolefin obtained by polymerizing a monomer component containing a fossil fuel-derived olefin; A resin composition comprising: The polyolefin (B) contains a modified polyolefin (B-1), A resin composition comprising the structural unit derived from ethylene (x) in an amount of 50 mass % or more based on the entire resin composition.
[0009] [2] The resin composition according to item [1], wherein the modified polyolefin (B-1) is graft-modified with at least one compound (y) selected from the group consisting of unsaturated carboxylic acids and derivatives thereof.
[0010] [3] The resin composition according to item [2], wherein the compound (y) is at least one compound selected from the group consisting of maleic anhydride and its derivatives, and the modified polyolefin (B-1) is a modified ethylene polymer containing structural units derived from the compound (y) in an amount of 0.01% by mass or more and 5% by mass or less, calculated as structural units derived from maleic anhydride.
[0011] [4] The resin composition according to item [2] or [3], wherein in the modified polyolefin (B-1), a content ratio of ethylene-derived structural units in all structural units excluding structural units derived from the compound (y) is 80 to 100 mol %.
[0012] [5] The resin composition according to any one of items [1] to [4], wherein the polyolefin (B) comprises the modified polyolefin (B-1) and a fossil fuel-derived polyolefin (B-2) obtained by polymerizing a monomer component comprising at least one selected from the group consisting of ethylene and α-olefins derived from fossil fuels.
[0013] [6] The resin composition according to any one of items [1] to [5], wherein the content of the polyolefin (A) is 50 parts by mass or more and 95 parts by mass or less, and the content of the polyolefin (B) is 5 parts by mass or more and 50 parts by mass or less (wherein the total of the components (A) and (B) is 100 parts by mass).
[0014] [7] A molded article comprising the resin composition according to any one of items [1] to [6]. [8] The molded article according to item [7], wherein the molded article is a film. [9] The molded article according to item [7], wherein the molded article is a tube.
[10] The molded article according to item [7], wherein the molded article is a bottle.
[0015]
[11] A laminate having a layer containing the resin composition according to any one of items [1] to [6].
[12] A laminate film comprising the laminate according to item
[11] .
[13] A laminate tube comprising the laminate according to item
[11] .
[14] A laminated bottle comprising the laminate according to item
[11] . Effect of the Invention
[0016] According to the present invention, it is possible to provide a polyolefin resin composition containing a carbon-neutral polyolefin using biomass-derived ethylene, which is comparable in physical properties such as adhesiveness to resin compositions produced using raw materials obtained from conventional fossil fuels, and uses of the resin composition. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0017] The present invention will be described in detail below. The resin composition according to the present invention comprises a biomass-derived polyolefin (A) obtained by polymerizing a monomer component mainly composed of biomass-derived ethylene (x), and a fossil fuel-derived polyolefin (B) obtained by polymerizing a monomer component containing an olefin derived from a fossil fuel, wherein the polyolefin (B) comprises a modified polyolefin (B-1), and the structural unit derived from the ethylene (x) is contained in an amount of 50 mass% or more based on the total amount of the resin composition.
[0018] [Biomass-derived polyolefin (A)] The biomass-derived polyolefin (A) is a polyolefin obtained by polymerizing a monomer component mainly composed of biomass-derived ethylene (x), and may be a homopolymer of ethylene (x) or a copolymer of ethylene (x) and another monomer. The polyolefin (A) may be biodegradable. The phrase "mainly composed of biomass-derived ethylene (x)" means that the component having the largest proportion (mass%) among the monomer components that are the raw materials of the polyolefin (A) is ethylene (x) derived from biomass. The biomass-derived polyolefin (A) means that at least a part of the raw material is a raw material derived from biomass (for example, the ethylene (x)), but does not mean that all of the raw materials are derived from biomass.
[0019] Examples of other monomers besides ethylene (x) include ethylene derived from fossil fuels, α-olefins derived from fossil fuels, and α-olefins derived from biomass. Such other monomers may be used alone or in combination of two or more. Examples of the α-olefins include α-olefins having 3 to 20 carbon atoms, such as butene, hexene, and octene. The polyolefin (A) is preferably a copolymer of ethylene (x) derived from biomass and α-olefins derived from fossil fuels.
[0020] The ethylene (x) is, for example, ethylene produced from ethanol extracted and refined from plants such as corn and sugarcane. Since such biomass-derived ethylene (x) is used as a raw material monomer, the polyolefin obtained by polymerization is "biomass-derived." From the viewpoint of maintaining a high level of biomass degree (biomass-derived carbon concentration), it is more preferable that the ethylene component contained in the polyolefin (A) is made of biomass-derived ethylene (x).
[0021] In addition to the above, polyolefins (A) also include those produced by the biomass balance approach, in which waste plant and animal oils are converted into bionaphtha, which is then mixed with petroleum-derived naphtha and cracked to obtain olefins. For example, this includes biomass-derived ethylene (x) as well as α-olefins such as propylene.
[0022] The polyolefin (A) can be obtained, for example, by homopolymerizing ethylene using a high-pressure method, or by copolymerizing ethylene with an α-olefin comonomer such as butene, hexene, or octene using a solid catalyst or a metallocene catalyst, etc. Also, as the polyolefin (A), a commercially available product such as plant-derived polyethylene from Braskem can be used.
[0023] The resin composition of the present invention may contain two or more biomass-derived polyolefins (A) having different compositions. When two or more polyolefins (A) are contained, the "density of polyolefin (A)" refers to a value calculated as a weighted average, and the "MFR of polyolefin (A)" refers to a value calculated by logarithmic additivity rule.
[0024] The density of the polyolefin (A) is not particularly limited, but is preferably 0.900 g / cm 3 More than 0.932g / cm 3 Less than or equal to 0.910 g / cm 3 More than 0.925g / cm 3 In the present invention, the density is a value measured according to the method A of JIS K7112-1980 after annealing as described in JIS K6760-1995. 3 In the above cases, there is an advantage that the antiblocking property is more excellent. In addition, when the density of the polyolefin (A) is 0.932 g / cm 3 The following cases have the advantage of excellent impact resistance.
[0025] The melt flow rate (MFR) of the polyolefin (A) is not particularly limited, but is preferably 0.1 g / 10 min to 10 g / 10 min, more preferably 0.5 g / 10 min to 10 g / 10 min. In the present invention, the MFR of the polyolefin (A) is a value measured by the A method under the conditions of a temperature of 190 ° C and a load of 21.18 N in the method specified in JIS K7210-1995. When the MFR of the polyolefin (A) is 0.1 g / 10 min or more, there is an advantage that the resin generates less heat during film formation processing. In addition, when the MFR of the polyolefin (A) is 10 g / 10 min or less, there is an advantage that the bubble stability during inflation film formation processing is excellent.
[0026] The above "biomass degree" (carbon concentration derived from biomass) is the value of the C14 content obtained by a radiocarbon (C14) measurement method conforming to ASTM D6866. Carbon dioxide in the atmosphere contains a certain percentage of C14 (105.5 pMC), so it is known that the C14 content in plants that grow by absorbing carbon dioxide from the atmosphere, such as corn, is also about 105.5 pMC. It is also known that fossil fuels contain almost no C14.
[0027] Therefore, the percentage of carbon derived from biomass can be calculated by measuring the percentage of C14 in the total carbon atoms in the resin composition. In the present invention, when the content of C14 in the resin composition (pMC) is PC14, the content of carbon derived from biomass, Pbio, can be calculated as follows. Note that pMC is an abbreviation for Percent Modern Carbon. Pbio(%)=PC14 / 105.5×100
[0028] The biomass degree of the resin composition of the present invention calculated as above is preferably 50% or more, more preferably 55% or more. The biomass degree of the resin composition within the above range is preferable from the viewpoint of improving the biomass degree in the product when used in a packaging material.
[0029] In order to set the biomass degree of the resin composition of the present invention in the above-mentioned range, it is desirable to set the content of structural units derived from biomass-derived ethylene (x) in the resin composition of the present invention to 50 mass% or more, preferably 52 mass% or more, and more preferably 55 mass% or more, relative to the entire resin composition (100 mass%).
[0030] The polymerization method of polyolefin (A) is not particularly limited, and can be carried out by a conventionally known method. It is preferable to appropriately adjust the polymerization temperature and polymerization pressure according to the polymerization method and polymerization device. In addition, the polymerization device is also not particularly limited, and a conventionally known device can be used.
[0031] [Polyolefin derived from fossil fuels (B)] The fossil fuel-derived polyolefin (B) is a polyolefin obtained by polymerizing a monomer component containing an olefin derived from a fossil fuel, and includes a modified polyolefin (B-1), and preferably includes a modified polyolefin (B-1) and a fossil fuel-derived polyolefin (B-2) obtained by polymerizing a monomer component containing at least one selected from the group consisting of ethylene and α-olefins derived from a fossil fuel.
[0032] When the entire polyolefin (B) is taken as 100 mass%, the content of the modified polyolefin (B-1) is preferably 10 mass% or more and 100 mass% or less, more preferably 20 mass% or more and 80 mass% or less. When the content of the modified polyolefin (B-1) is within the above range, it is excellent in terms of the balance between adhesive strength and production costs.
[0033] <Modified polyolefin (B-1)> The modified polyolefin (B-1) is a modified polyolefin obtained by modifying at least a portion of an unmodified polyolefin, and is preferably a modified polyolefin obtained by graft-modifying with at least one compound (y) selected from the group consisting of unsaturated carboxylic acids and their derivatives.
[0034] <Unmodified polyolefin> The unmodified polyolefin is not particularly limited as long as it is a polyolefin obtained by polymerizing a monomer component containing an olefin derived from a fossil fuel, and preferably includes an ethylene homopolymer and a copolymer of ethylene and an α-olefin having 3 to 20 carbon atoms, more preferably an ethylene homopolymer and a copolymer of ethylene and an α-olefin having 3 to 10 carbon atoms, and even more preferably an ethylene homopolymer and a copolymer of ethylene and an α-olefin having 2 to 8 carbon atoms. The unmodified polyolefin may be used alone or in combination of two or more kinds.
[0035] Examples of the α-olefin include propylene, 1-butene, 1-pentene, 1-hexene, 1-octene, 1-decene, and 4-methyl-1-pentene. These may be used alone or in combination of two or more.
[0036] The density of the unmodified polyolefin is preferably 0.860 to 0.960 g / cm 3 , more preferably 0.865 to 0.955 g / cm 3 , more preferably 0.870 to 0.950 g / cm 3 The unmodified polyolefin preferably has a melt flow rate (MFR) of 0.01 to 100 g / 10 min, more preferably 0.05 to 50 g / 10 min, and even more preferably 0.1 to 10 g / 10 min, according to ASTM D1238 at 190° C. under a load of 2.16 kg. If the density and MFR of the unmodified polyolefin are within this range, the density and MFR of the modified polyolefin (B-1) will also be approximately the same, making it easy to handle.
[0037] The unmodified polyolefin can be produced by any conventionally known method, for example, by a high-pressure method or a low-pressure method using a titanium catalyst, a vanadium catalyst, a metallocene catalyst, etc. The unmodified polyolefin may be in the form of either a resin or an elastomer, and both an isotactic structure and a syndiotactic structure can be used, and there is no particular restriction on the stereoregularity. Commercially available resins can also be used as they are.
[0038] ≪Compound (y)≫ At least one compound (y) selected from the group consisting of unsaturated carboxylic acids and derivatives thereof, which is used for graft modification, can include unsaturated compounds having one or more carboxylic acid groups, unsaturated compounds having one or more carboxylic anhydride groups and derivatives thereof, and examples of the unsaturated groups of the unsaturated compounds include vinyl groups, vinylene groups, unsaturated cyclic hydrocarbon groups, etc. Specific examples of the compounds include unsaturated carboxylic acids such as acrylic acid, methacrylic acid, maleic acid, fumaric acid, tetrahydrophthalic acid, itaconic acid, citraconic acid, crotonic acid, isocrotonic acid, norbornene dicarboxylic acid, and bicyclo[2,2,1]hept-2-ene-5,6-dicarboxylic acid, or acid anhydrides or derivatives thereof (e.g., acid halides, amides, imides, esters, etc.).
[0039] Specific examples of compound (y) include malenyl chloride, malenylimide, maleic anhydride, itaconic anhydride, citraconic anhydride, tetrahydrophthalic anhydride, bicyclo[2,2,1]hept-2-ene-5,6-dicarboxylic anhydride, dimethyl maleate, monomethyl maleate, diethyl maleate, diethyl fumarate, dimethyl itaconate, diethyl citraconic acid, dimethyl tetrahydrophthalate, dimethyl bicyclo[2,2,1]hept-2-ene-5,6-dicarboxylate, hydroxyethyl(meth)acrylate, hydroxypropyl(meth)acrylate, glycidyl(meth)acrylate, aminoethyl methacrylate, and aminopropyl methacrylate. Compound (y) may be used alone or in combination of two or more. Among these, maleic anhydride, (meth)acrylic acid, itaconic anhydride, citraconic anhydride, tetrahydrophthalic anhydride, bicyclo[2,2,1]hept-2-ene-5,6-dicarboxylic anhydride, hydroxyethyl (meth)acrylate, glycidyl methacrylate, and aminopropyl methacrylate are preferred, and dicarboxylic anhydrides such as maleic anhydride, itaconic anhydride, citraconic anhydride, tetrahydrophthalic anhydride, and bicyclo[2,2,1]hept-2-ene-5,6-dicarboxylic anhydride are more preferred, with maleic anhydride being particularly preferred.
[0040] As a method for introducing compound (y) into unmodified polyolefin, a well-known method can be adopted, and examples thereof include a method of graft copolymerizing compound (y) onto the main chain of unmodified polyolefin, and a method of radically copolymerizing an olefin with compound (y), etc.
[0041] Graft polymerization method When the modified polyolefin (B-1) is obtained by graft copolymerization, the compound (y) and, if necessary, other ethylenically unsaturated monomers and the like are graft copolymerized onto the unmodified polyolefin that serves as the graft main chain in the presence of a radical initiator.
[0042] The method of grafting the compound (y) to the main chain of the unmodified polyolefin is not particularly limited, and a conventionally known graft polymerization method such as a solution method or a melt kneading method can be adopted. For example, a method of dissolving the unmodified polyolefin in an organic solvent, then adding the compound (y) and, if necessary, a radical initiator such as an organic peroxide to the obtained solution, and reacting for 0.5 to 15 hours, preferably 1 to 10 hours, usually at a temperature of 60 to 350 ° C., preferably 80 to 190 ° C., or a method of adding the unmodified polyolefin, the compound (y) and, if necessary, a radical initiator such as an organic peroxide, without a solvent, using an extruder or the like, and reacting for 0.5 to 10 minutes at a temperature above the melting point of the unmodified polyolefin, preferably 120 to 350 ° C.
[0043] <Characteristics of Modified Polyolefin (B-1)> The content (graft amount) of the structural unit derived from the compound (y) in the modified polyolefin (B-1) is, for example, preferably 0.01% by mass or more and 5% by mass or less, preferably 0.05% by mass or more and 4.0% by mass or less, more preferably 0.1% by mass or more and 3.0% by mass or less, calculated as the structural unit derived from maleic anhydride, when the compound (y) is at least one compound selected from the group consisting of maleic anhydride and its derivatives. The same applies when the compound (y) is another compound. If the graft amount exceeds the above range, it becomes uneconomical, while if the graft amount in the modified polyolefin (B-1) is less than the above range, the adhesive strength tends to be small.
[0044] In the modified polyolefin (B-1), the content ratio of the structural units derived from ethylene in all structural units excluding the structural units derived from the compound (y) is preferably 80 mol% or more and 100 mol% or less, more preferably 85 mol% or more and 100 mol% or less, and even more preferably 95 mol% or more and 100 mol% or less. When the content ratio of the structural units derived from ethylene is within the above range, it is excellent in terms of moldability.
[0045] The melt flow rate (MFR) of the modified polyolefin (B-1) at 190°C under a load of 2.16 kg according to ASTM D1238 is preferably 0.01 g / 10 min to 500 g / 10 min, more preferably 0.05 g / 10 min to 100 g / 10 min. When the MFR of the modified polyolefin (B-1) is within the above range, the moldability is good and the adhesive strength is also excellent. In a method in which an adhesive layer having a thickness of 100 microns is sandwiched between substrates by hot press molding and a peel test is performed to measure the adhesive strength, the lower the MFR and the longer the molecular chain, the higher the adhesive strength tends to be. In a film molded by cast molding, the adhesive layer having a thickness of 30 to 50 microns has the opposite tendency. In a method in which a cast molding film peel test is performed to measure the adhesive strength, the higher the MFR and the shorter the molecular chain, the higher the adhesive strength tends to be. This is thought to be because the higher the MFR and the shorter the molecular chain, the better the flowability at the interface.
[0046] The density of the modified polyolefin (B-1) is preferably 0.860 g / cm 3 More than 0.960g / cm 3 Less than or equal to 0.865 g / cm 3 More than 0.955g / cm 3 More preferably, 0.870 g / cm 3 More than 0.950g / cm 3 The following is the result.
[0047] <Polyolefin derived from fossil fuels (B-2)> The fossil fuel-derived polyolefin (B-2) is a polyolefin obtained by polymerizing a monomer component containing at least one selected from the group consisting of ethylene and α-olefins derived from fossil fuels.
[0048] The polyolefin (B-2) may be the same as the unmodified polyolefin described above, and is preferably an ethylene homopolymer or a copolymer of ethylene and an α-olefin having 3 to 20 carbon atoms, more preferably a copolymer of ethylene and an α-olefin having 3 to 10 carbon atoms, and even more preferably a copolymer of ethylene and an α-olefin having 2 to 8 carbon atoms.
[0049] The density of the polyolefin (B-2) is preferably 0.860 to 0.960 g / cm 3 , more preferably 0.862 to 0.955 g / cm 3 , more preferably 0.865 to 0.950 g / cm 3 The polyolefin (B-2) has a melt flow rate (MFR) according to ASTM D1238 at 190° C. under a load of 2.16 kg of preferably 0.01 to 100 g / 10 min, more preferably 0.05 to 50 g / 10 min, and further preferably 0.1 to 10 g / 10 min.
[0050] Polyolefin (B-2) can be produced by any conventionally known method, for example, by a high pressure method or a low pressure method using a titanium catalyst, a vanadium catalyst, a metallocene catalyst, etc. Polyolefin (B-2) may be in the form of either a resin or an elastomer, and both isotactic structure and syndiotactic structure can be used, and there is no particular restriction on stereoregularity. Commercially available resins can also be used as they are.
[0051] [Other ingredients] The resin composition of the present invention may contain, as necessary, additives commonly used such as antioxidants, weather stabilizers, antistatic agents, antifogging agents, antiblocking agents, lubricants, nucleating agents, pigments, or other polymers or rubbers, within the scope of the object of the present invention.
[0052] [Composition of resin composition] In the resin composition of the present invention, when the total amount of the components (A) and (B) is 100 parts by mass, The content of the biomass-derived polyolefin (A) is preferably 50 parts by mass or more and 95 parts by mass or less, more preferably 55 parts by mass or more and 90 parts by mass or less, and even more preferably 60 parts by mass or more and 85 parts by mass or less, The content of the fossil fuel-derived polyolefin (B) is preferably 5 parts by mass or more and 50 parts by mass or less, more preferably 10 parts by mass or more and 45 parts by mass or less, and even more preferably 15 parts by mass or more and 40 parts by mass or less. When the contents of the biomass-derived polyolefin (A) and the fossil fuel-derived polyolefin (B) are within the above ranges, a resin composition having a high biomass content can be obtained.
[0053] The resin composition of the present invention can be prepared by various known methods, such as a method of dry blending the components (A) and (B) and, if necessary, other components, using a Henschel mixer, a tumbler blender, a V-blender or the like, a method of dry blending and then melt kneading using a single-screw extruder, a multi-screw extruder, a Banbury mixer or the like, and a method of stirring and mixing in the presence of a solvent.
[0054] [Laminate] The laminate of the present invention has a layer (I) (hereinafter also referred to as "adhesive layer (I)") containing the above-mentioned resin composition of the present invention, and preferably further has a layer (II) containing at least one polymer selected from the group consisting of polyamide, saponified ethylene-vinyl acetate copolymer (EVOH), and polyester. In this case, it is preferable that the layer (II) is directly laminated to the layer (I). Furthermore, the laminate of the present invention particularly preferably further has a base layer (III) made of polyethylene. In this case, it is preferable that the layer (I) is directly laminated to the base layer (III).
[0055] The polyamide contained in the layer (II) is not particularly limited, but examples thereof include nylon 6, nylon 66, nylon 610, nylon 12, nylon 11, MXD nylon, amorphous nylon, and copolymer nylon.
[0056] The saponified ethylene-vinyl alcohol copolymer (EVOH) contained in the layer (II) is preferably a polymer having a saponification degree of 90 to 100%, preferably 95 to 100%, obtained by saponifying an ethylene-vinyl acetate copolymer having an ethylene content of 15 to 60 mol%, preferably 20 to 50 mol%.
[0057] The polyester contained in the layer (II) is not particularly limited, but may be selected from, for example, polylactic acid, polyethylene terephthalate, polybutylene terephthalate, polyethylene naphthenate, mixtures of these resins, or aromatic polyesters such as liquid crystal polymers.
[0058] The polyethylene contained in the base layer (III) is not particularly limited, and any known polyethylene can be used.
[0059] Examples of layer configurations of the laminate of the present invention include a two-layer structure of layer (II) / adhesive layer (I), a three-layer structure of layer (II) / adhesive layer (I) / layer (II), a three-layer structure of base layer (III) / adhesive layer (I) / layer (II), a three-layer structure of adhesive layer (I) / layer (II) / adhesive layer (I), and a five-layer structure of base layer (III) / adhesive layer (I) / layer (II) / adhesive layer (I) / base layer (III).
[0060] In addition, the laminate of the present invention may contain layers other than the above-mentioned layer (I), layer (II), and base layer (III) as long as the effects of the present invention are not impaired. Examples of the other layers include layers made of metals such as aluminum, iron, copper, tin, and nickel, layers made of alloys containing at least one of these metals as a main component, and regrind layers. The regrind layer is a layer made of burrs (unnecessary parts) generated when molding the laminate, recovered laminates (scrap), and defective products generated during molding, which are crushed, or, if necessary, the crushed products are melt-kneaded in an extruder or the like (regrind). Such other layers can also be used instead of the layer (III).
[0061] The above-mentioned layers constituting the laminate of the present invention may contain known additives such as fillers, stabilizers, lubricants, antistatic agents, flame retardants, and foaming agents, within the scope of the present invention. The laminate of the present invention may be produced by known methods such as coextrusion molding, press molding, and extrusion lamination molding. Among these, the coextrusion molding method is preferred in terms of interlayer adhesion. Coextrusion molding methods include the T-die method using a flat die and the inflation method using a circular die. The flat die may be either a single manifold type or a multi-manifold type using a black box. A known die may also be used for the inflation method.
[0062] [Application] The resin composition according to the present invention, a molded article (for example, a film, a tube, a bottle, etc.) containing the resin composition, a laminate having a layer containing the resin composition, and a laminated film, a laminated tube, a laminated bottle, etc. containing the laminate can be suitably used for packaging products such as food containers and bags, cosmetic containers, sheets and packaging products, and pharmaceutical containers, sheets and packaging products, etc. They can also be suitably used for various applications such as optical films, resin plates, various label materials, lid materials, and laminate tubes, and are particularly preferably used for packaging products and sheet molded products. EXAMPLES
[0063] The present invention will be described in more detail below with reference to examples, but the present invention is not limited to these examples in any way.
[0064] [Method of measuring physical properties] In the examples and comparative examples, physical properties (density and melt flow rate) were measured by the following methods.
[0065] <Density (g / cm 3 )> Density was measured according to ASTM D1505.
[0066] <Melt flow rate (MFR) (g / 10 min)> The melt flow rate was measured in accordance with ASTM D1238 at a temperature of 190° C. and a load of 2160 g.
[0067] [Materials used] The polyolefins used in the examples and comparative examples are shown below. Note that all of the polyolefins used were commercially available products.
[0068] <Polyethylene> PE-1: Biomass-derived linear low-density polyethylene (manufactured by Braskem SA, biomass content: 87% (ASTM D6866 compliant), density: 0.92 g / cm 3, MFR:2.3g / 10min) PE-2: Linear low-density polyethylene derived from fossil fuels (Prime Polymer Co., Ltd., density: 0.92 g / cm 3 , MFR: 2.0g / 10min)
[0069] <Maleic anhydride modified polyethylene> MAH-PE-1: fossil fuel-derived maleic anhydride-modified linear low-density polyethylene (Mitsui Chemicals, Inc., maleic anhydride graft amount: 1 mass%, density: 0.92 g / cm 3 , MFR:0.3g / 10min)
[0070] <Ethylene / α-olefin random copolymer> EBR-1: Ethylene-1-butene random copolymer derived from fossil fuels (Mitsui Chemicals, Inc., density: 0.87 g / cm 3 , MFR: 3.6g / 10min)
[0071] [Example 1] <Preparation of Resin Composition> A mixture of 65% by mass of polyethylene (PE-1) as polyolefin (A), 15% by mass of maleic anhydride modified polyethylene (MAH-PE-1) as modified polyolefin (B-1), and 20% by mass of ethylene-α-olefin random copolymer (EBR-1) as polyolefin (B-2) was kneaded and granulated in a 60 mmφ single screw extruder set at 220°C to obtain a resin composition. The resulting resin composition had a density of 0.91 g / cm. 3 and the MFR was 1.9 g / 10 min.
[0072] <Production of Laminate> A three-layer laminate (film) consisting of a PE layer (III) formed from linear low-density polyethylene (UltZex 2021L, manufactured by Prime Polymer Co., Ltd.), an adhesive layer (I) formed from the obtained resin composition, and an EVOH layer (II) formed from an ethylene-vinyl alcohol copolymer (EVAL F101A, manufactured by Kuraray Co., Ltd.) laminated in this order was produced under the following molding conditions.
[0073] <Laminate molding conditions> Layer structure: PE layer (III) / adhesive layer (I) / EVOH layer (II) Layer thickness: PE layer (III) 40 μm Adhesive layer (I) 10μm EVOH layer (II) 20μm T-die molding machine: PE layer (III) 40mmφ extruder, set temperature 220℃ Adhesive layer (I): 30 mm diameter extruder, set temperature 220°C EVOH layer (II) 30mmφ extruder, set temperature 220℃ Molding speed: 20m / min
[0074] <Adhesive strength (N / 15mm)> The adhesive strength of the obtained laminate (three-layer film) was measured by cutting a sample with a width of 15 mm from the laminate, and measuring the interlayer adhesive strength (peel strength) between the adhesive layer (I) and the EVOH layer (II) using a tensile tester (IM-20ST type, manufactured by Intesco Corporation) in a thermostatic chamber at 23°C. The measurement method for the peel test was the T-peel method, and the peel speed was 300 mm / min. This measurement was performed five times, and the average of the obtained values was taken as the adhesive strength (EVOH adhesive strength) of the laminate. The results are shown in Table 1.
[0075] [Comparative Example 1] A resin composition was prepared in the same manner as in Example 1, except that the compounding recipe was changed as shown in Table 1. The resulting resin composition had a density of 0.91 g / cm 3 The MFR was 1.7 g / 10 min. Using the obtained resin composition, a laminate was produced in the same manner as in Example 1, and the adhesive strength was measured. The results are shown in Table 1.
[0076] [Table 1]
[0077] As shown in Table 1, the adhesive strength of the laminate of Example 1 produced using biomass-derived polyethylene was comparable to the adhesive strength of the laminate of Comparative Example 1 produced only using petroleum fuel-derived polyethylene.
Claims
1. A biomass-derived polyolefin (A) obtained by polymerizing a monomer component mainly composed of biomass-derived ethylene (x); A fossil fuel-derived polyolefin (B) obtained by polymerizing a monomer component containing an olefin derived from a fossil fuel (not including a monomer component derived from biomass); A resin composition comprising: the polyolefin (B) comprises a modified polyolefin (B-1) and a fossil fuel-derived polyolefin (B-2) which is a copolymer of a monomer component containing at least one selected from the group consisting of fossil fuel-derived ethylene and fossil fuel-derived α-olefins having 3 to 20 carbon atoms; The unmodified polyolefin before the modification of the modified polyolefin (B-1) is an ethylene homopolymer or a linear low-density polyethylene, The resin composition contains the structural unit derived from ethylene (x) in an amount of 50 mass% or more based on the entire resin composition.
2. The resin composition according to claim 1, wherein the modified polyolefin (B-1) is graft-modified with at least one compound (y) selected from the group consisting of unsaturated carboxylic acids and derivatives thereof.
3. The compound (y) is at least one compound selected from the group consisting of maleic anhydride and its derivatives, and the modified polyolefin (B-1) contains a structural unit derived from the compound (y) in an amount of 0.01% by mass or more and 5% by mass or less in terms of a structural unit derived from maleic anhydride. The resin composition according to claim 2.
4. The modified polyolefin (B-1) has a content ratio of ethylene-derived structural units in all structural units excluding the structural units derived from the compound (y) of 80 to 100 mol%. The resin composition according to claim 2 or 3.
5. The content of the polyolefin (A) is 50 parts by mass or more and 95 parts by mass or less, and the content of the polyolefin (B) is 5 parts by mass or more and 50 parts by mass or less (wherein the total of the components (A) and (B) is 100 parts by mass). The resin composition according to any one of claims 1 to 4.
6. A molded article comprising the resin composition according to any one of claims 1 to 5.
7. The molded article according to claim 6, wherein the molded article is a film.
8. The molded article according to claim 6, wherein the molded article is a tube.
9. The molded article according to claim 6, wherein the molded article is a bottle.
10. A laminate comprising a layer containing the resin composition according to any one of claims 1 to 5.
11. A laminate film comprising the laminate according to claim 10.
12. A laminate tube comprising the laminate according to claim 10.
13. A laminated bottle comprising the laminate of claim 10.
Citation Information
Patent Citations
Laminated film and packaging bag made of the film
JP2006015605A
Film employing plant-derived polyethylene, and container and packaging bag
JP2012167172A
Plastic film
JP2013091259A
Hollow synthetic resin sheet and box containing the same
JP2015150871A
Multilayer structure
JP2021045963A